Oxford textbook of sleep disorders - Chokroverty, Sudhansu; Ferini-Strambi, Luigi (Oxford University Press, 2017)
There has been a rapid global increase in the number of individuals making sleep medicine their career, resulting in an explosive growth in the number of sleep centres and programmes, as well as an increasing number of sleep societies and journals. Part of the Oxford Textbooks in Clinical Neurology series, the Oxford Textbook of Sleep Disorders covers the rapid advances in scientific, technical, clinical, and therapeutic aspects of sleep medicine which have captivated sleep scientists and clinicians. This text aims to introduce sleep disorders within the context of classical neurological diseases, giving an in-depth coverage of the topic in a logical and orderly way, while emphasizing the practical aspects in a succinct and lucid manner. Divided into 12 sections, this book begins by discussing the basic science (Section 1), before moving onto the laboratory evaluation (Section 2) and the clinical science (Section 3). The remainder of the book focuses on specific sleep disorders (Sections 4-12), from insomnias and parasomnias to sleep neurology and sleep and psychiatric disorders. Chapters are supplemented by tables, case reports, and illustrations intended to succinctly provide relevant information in a practical manner for diagnosis and treatment of sleep disorders, while always emphasizing clinical-behavioural-laboratory correlations.
Oxford textbooks in clinical neurology
Keywords: Sleep Wake Disorders; Clinical Medicine; klinické lékařství; poruchy spánku a bdění; neurologie